Pengaruh Sosial Media Marketing, Ekuitas Merek, Dan Citra Destinasi Terhadap Minat Berkunjung Ke Tempat Wisata - Isman Isman; Ryan Gerry Patalo; Dimas Eka Pratama (Jurnal Studi Manajemen dan Bisnis, 2020)
Jatim Park 3 is a tourist destination in Batu City with the concept of a blend of tourism and education. There are several rides in Jatim Park 3, namely; Dino Park, Indonesian Music Gallery, Fun Tech Plaza, 6D Cinema, etc. Social media marketing trends are also found in the tourism industry in Indonesia and Jawa Timur Park 3 is a new place of entertainment and education in Batu Tourism City which is not yet widely known by the general public, considering that this tourist spot was only inaugurated in November 2017. So that JTP 3 needs to be vigorous to carry out marketing activities to introduce its products to the wider community. The purpose of this study was to determine the effect of social media marketing, Brand Equity and destination image on visiting interests. The population in this study were all followers of Jatim Park 3 social media accounts in the form of facebook, by taking a sample of 150 people. Multiple linear regression and hypothesis testing are the analytical methods used, and the results of the research show that social media marketing influences visiting interests. Brand Equity / Brand Equity affects the interest in visiting. Destination image has no significant effect on visiting interest.